The creativity and passion of the private sector [in ICT4Ag] - Gonnet, Julien; Kahumbu Stephanou, Su (Technical Centre for Agricultural and Rural Cooperation, 2015)
The private sector is well placed to contribute to the agricultural sector through its creativity and passion in partnership with other players in the sector.